ANALISIS PERBEDAAN GENDER DALAM TINGKAT KEDISIPLINAN BELAJAR MAHASISWA DI MASA PANDEMI COVID 19 - Wahyuningsih, Nur Eka (Pusat Studi Gender dan Anak, IAIN Palu, 2020)
This study entitled the analysis of gender differences in the level of student learning discipline during the Covid 19 pandemic. The purpose of this study was to analyze differences in the level of student learning discipline and the level of learning discipline among female students in the education department in Palu City during the covid pandemic 19. The research approach used is quantitative research through the survey method, namely research used to obtain data that occurred in the past or present, regarding beliefs, opinions, characteristics, behavior, variable relationships and to test several hypotheses about sociological and psychological variables from the sample drawn from a specific population. Data collection techniques in this study using a questionnaire. Technique of data analysis through independent sample T-test. The population in this study were students majoring in education in the city of Palu. The technique used in sampling in this study was purposive random sampling technique. The results showed that there was no difference in the level of student learning discipline and the level of learning discipline among female students during the Covid 19 pandemic. This can be seen from the sig (2-tailed) value of 0.573> 0.05, so Ho is accepted and Ha is rejected. This means that students have the same opportunities, both men and women in terms of discipline in learning.